Associations Between High-Sensitivity C-Reactive Protein and All-Cause Mortality Among Oldest-Old in Chinese Longevity Areas: A Community-Based Cohort Study - Chen, Pei-Liang; Li, Zhi-Hao; Yang, Hai-Lian; Cao, Zhao-Jin; Cheng, Xin; Zhao, Feng; Zhang, Xi-Ru; Lv, Yue-Bin; Li, Fu-Rong; Zhou, Yuan-Feng; Li, Hao-Nan; Qu, Ying-Li; et al. (Frontiers in Public Health, 2022)
Background: The association high-sensitivity C-reactive protein (hsCRP) levels and all-cause mortality for the oldest-old (aged 80 years or older) remains unclear. We aimed to investigate the associations between hsCRP concentrations and the risks of all-cause mortality, and further identify the potential modifying factors affecting these associations among the oldest-old. Methods: This prospective, community-based cohort study included 2206 participants aged 80 years or older (median age 93.0 years) from the Healthy Aging and Biomarkers Cohort Study. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) with 95% confidential intervals (95% CIs) for all-cause mortality according to hsCRP quartiles and recommendation for relative risk categories of hsCRP levels (< 1.0, 1.0-3.0 and > 3.0 mg/L), with adjustment for sociodemographic information, lifestyle, physical examination, medical history and other potential confounders. Results: During a median follow-up period of 3.1 years (IQR: 1.6-3.9 years), 1106 deaths were verified. After full adjustment for potential confounders, a higher hsCRP concentration was positively associated with an increased risk of all-cause mortality (P for trend < 0.001). Compared with the lowest quartile, the fully adjusted HRs of the second, third, and fourth quartiles were 1.17 (95% CI: 0.94, 1.46), 1.28 (95% CI: 1.01, 1.61), and 1.50 (95% CI: 1.20, 1.87), respectively. Similar trend was observed stratified by hsCRP levels, in which individuals with hsCRP > 3.0 mg/L (high risk) had a significantly higher risk (HR: 1.39; 95% CI: 1.15, 1.70) of all-cause mortality. The association of hsCRP with all-cause mortality was modified by smoking status (P for interaction < 0.05). Conclusions: Our study indicated that elevated hsCRP concentrations are associated with a higher risk of all-cause mortality among Chinese oldest-old. Future studies investigating additional factors of disease and aging processes are needed to obtain a better understanding of the mechanisms.